EQUITY FINANCING OPTIONS AND FINANCIAL PERFORMANCE OF LISTED MANUFACTURING FIRMS IN NIGERIA - Olufemi Adebola Owolabi, Adebola Daniel Kolawole, Oluyinka Isaiah Ogungbade, Adeleke Clement Adekoya (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study empirically assessed the effect of equity financing options on financial performance of listed manufacturing firms in Nigeria. Secondary data were obtained from purposively selected 60 out of the 70 listed manufacturing firms. Return on assets (ROA) was used to measure performance while the equity finance options used in the study are; retained earnings, ordinary share capital and preference shares. The overall effect of all the independent variables are statistically significant in explaining the variation in return on assets as their individual probability values are less than 0.05 level of significance. The individual effect of each of the explanatory variables reveals that retained earnings and preference shares significantly influence performance listed manufacturing firms in Nigeriagiven its probability value of 0.000 which is less than 5%. Although, the effect of ordinary share capital on performance of listed manufacturing firms in Nigeria was positive but statistically insignificant with a probability value of 5%.The study thus concluded thatequity financing option composition significantly affect financial performance of listed manufacturing firms in Nigeria.